Electromagnetic Emissions from Wireless Power Transfer System - Baikova, Elena (2016)
In this paper, the measurement and analysis of the electromagnetic radiated emissions from the wireless power transfer system is reported. The aim is to evaluate the level of the electromagnetic field produced by the magnetic resonance wireless power transfer system. Due to the advances of the wireless power transfer technology, it becomes feasible to apply the wireless power transfer in the electric vehicles charging. Among the existent wireless power transfer technologies, the magnetic resonant coupling is proven to be the most suitable for this task. Because of strong electromagnetic field generated by wireless power transfer system the electromagnetic compatibility has become an important issue.